Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00709-005-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of endocytosis in pollen tube growth by phosphoinositides and phospholipids

Abstract: In plants, tip-growing cells represent an ideal system to investigate signal transduction mechanisms, and among those, pollen tubes are one of the favourite models. Many signalling pathways have been identified during germination and tip growth, namely, Ca2+, calmodulin, phosphoinositides, cyclic AMP, and GTPases. Not surprisingly, the apical secretory machinery, essential for tip growth, seems to be an intersection point for all these pathways. Recently, the phospholipid phosphatidic acid was also suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…We also show that Arabidopsis Atg6/Vps30 partially complemented VPS function in atg6/vps30 mutant yeast. Several other Arabidopsis VPS homologs are required in pollen tubes (Hicks et al, 2004;Lobstein et al, 2004) because the polarized growth of pollen tubes requires membrane trafficking (Hepler et al, 2001;Monteiro et al, 2005). We found that disruption of AtATG6/VPS30 resulted in male sterility because the mutant pollen did not germinate.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…We also show that Arabidopsis Atg6/Vps30 partially complemented VPS function in atg6/vps30 mutant yeast. Several other Arabidopsis VPS homologs are required in pollen tubes (Hicks et al, 2004;Lobstein et al, 2004) because the polarized growth of pollen tubes requires membrane trafficking (Hepler et al, 2001;Monteiro et al, 2005). We found that disruption of AtATG6/VPS30 resulted in male sterility because the mutant pollen did not germinate.…”
mentioning
confidence: 79%
“…Extensive studies have identified several key components for pollen tube growth; one of these is vesicular trafficking (Hepler et al, 2001;Monteiro et al, 2005). The tip of the pollen tube contains numerous vesicles that could provide precursor materials for the rapidly expanding cell wall of the growing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports support a role for both PI4P and PI(4,5)P 2 in the regulation of tip growth in root hairs and pollen tubes (Monteiro et al, 2005a(Monteiro et al, , 2005bDowd et al, 2006;Helling et al, 2006;Preuss et al, 2006;Ischebeck et al, 2008;Kusano et al, 2008;Sousa et al, 2008;Stenzel et al, 2008;Thole et al, 2008;Szumlanski and Nielsen, 2009), but the mechanism by which these membrane-localized signaling molecules affect polarized cell growth remained unclear. Our results support the hypothesis that both PI4P and PI(4,5)P 2 play a critical role in the regulation of clathrin-dependent endocytosis at the tip of pollen tubes and that a proper balance between PI4P and PI(4,5)P 2 accumulation in the apical PM is important for clathrindependent endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that these PIP5Ks affect either pectin exocytosis or recycling of endocytic vesicles Sousa et al, 2008). Although several studies have implicated phosphoinositides in the regulation of endocytosis in pollen tubes (Monteiro et al, 2005a(Monteiro et al, , 2005bHelling et al, 2006;Sousa et al, 2008), the role and the mode of action for phosphoinositides in endocytosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, regulatory functions described for PtdIns(4,5)P 2 include some of those required for a regulator of growth processes in tip-growing cells. PtdIns(4,5)P 2 has previously been demonstrated to be involved in tip growth processes in pollen tubes (Kost et al, 1999;Monteiro et al, 2005;Dowd et al, 2006), a tip-growing system sharing some components of the growth machinery with root hairs (Song et al, 2006). In pollen tubes, Rac-type Rho proteins in the tip plasma membrane physically associate with an enzyme activity producing PtdIns(4,5)P 2 (Kost et al, 1999), and PtdIns(4,5)P 2 has been visualized in a plasma membrane microdomain of the pollen tube tip (Kost et al, 1999).…”
Section: Introductionmentioning
confidence: 99%